Diseño de un sistema de control de inventarios en la distribuidora de pollos "Jodispol" por el periodo económico 2022-2023 que permita una gestión eficiente en el manejo del producto - Muso Flores, Cristopher Aníbal (2023)
This integrating project was developed in the "JODISPOL" Chicken Distributor, dedicated to the purchase and sale of chickens; The problem of the entity lies in the lack of an inventory control system, since there are no established policies and procedures for product management, stock levels, storage as well as the commercial process, that is, purchases and sales, the lack of inventory management, does not allow it to have a reliable value. Therefore, the objective of the project is to design an inventory control system that allows efficient management in the handling of the product.